Peran ASEAN Merespons Kerja Sama Militer Amerika Serikat dan Filipina Terkait Konflik Laut Cina Selatan - Abdul Musyawardi Chalid; Dudy Heryadi; Nuraeni Suparman; Arfin Surdirman (Intermestic: Journal of International Studies, 2016)
ASEAN is facing a complex problem when the interverence of two great powers, China and United States of America, expanded their influences in Southeast Asia. Both states gave their influence in the dynamic of South China Sea dispute. One of ASEAN member states that has interest on the claim of South China Sea was the Philippines. The Philippines and United States of America military cooperation triggered China to give their responses and made the conflict resolution became more complicated. This research aim to look at ASEAN role in dealing with the problem of two great powers related to one of ASEAN member. This research was using qualitative method. The research used the concept of the role of international organization. Analysis was conducted by using data interpretation on literature review.